2000
DOI: 10.1111/j.1530-0277.2000.tb04574.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Exposure Enhances Apoptosis Within the Testes

Abstract: All of these observations suggest that ethanol enhances testicular germ cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 62 publications
5
43
0
Order By: Relevance
“…In addition, numerous studies showed that apoptosis was an important mechanism by which ethanol caused tissue injury [27,28]. Recently, Zhu et al firstly showednumerous studies showed that apoptosis was an important mechanism by which ethanol caused tissue injury that chronic ethanol exposure enhanced apoptosis of testicular germ cells and measured expression of some apoptosis-related proteins such as Bcl-2, p53 and Fas ligand [19]. During the time of writing this paper, Eid et al suggested that Fas system might involve in germ cell apoptosis in rats treated with chronic ethanol for 12 weeks [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, numerous studies showed that apoptosis was an important mechanism by which ethanol caused tissue injury [27,28]. Recently, Zhu et al firstly showednumerous studies showed that apoptosis was an important mechanism by which ethanol caused tissue injury that chronic ethanol exposure enhanced apoptosis of testicular germ cells and measured expression of some apoptosis-related proteins such as Bcl-2, p53 and Fas ligand [19]. During the time of writing this paper, Eid et al suggested that Fas system might involve in germ cell apoptosis in rats treated with chronic ethanol for 12 weeks [29].…”
Section: Discussionmentioning
confidence: 99%
“…One is that ethanol metabolism produces an oxidative stress within the testes [15]; another is that ethanol exposure changes either testosterone [16] or esterone levels [17]. In addition, Zhu et al showed that ethanol exposure adversely affected the secretory function of Sertoli cells [18] and their recent research revealed enhanced apoptosis within the testes after chronic ethanol exposure [19]. However, it is still not clear how ethanol can lead to testicular injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Numerous studies [8][9][10] have indicated that chronic alcohol abuse in males resulted in decreased testosterone production, reduced sperm output, and testis atrophy. In animals, ethanol exposure of adults can increase germ cell apoptosis 11 and cause an adverse effect on the secretory function of Sertoli cells. 12 Traditionally, palm wine is given to women after childbirth to help stimulate the production of milk as well as to young women in fattening rooms.…”
Section: Introduction Pmentioning
confidence: 99%
“…Degeneration of germinal epithelium in rats (Rattus norvegicus) and mice (Mus musculus) in response to hypophysectomy, gonadotrophin and GnRH antibody administration, severe temperature stress, and toxin exposure is associated with increased apoptotic cell death (Tapanainen et al, 1993;Hikim et al, 1995;Shetty et al, 1996;Lee, et al, 1997). Indeed, most studies of testicular apoptosis have examined pathological or supraphysiological states (for example, Franca et al, 2000;Zhu et al, 2000). Seasonal gonadal atrophy represents a natural model for the study of gonadal apoptosis.…”
mentioning
confidence: 99%